Exploring the use of crowd generated geospatial content in improving the quality of ecological feature mapping - Kinley, Laura Rhiannon (2016)
Generalisation and uncertainty in ecological data are hugely problematic for environmental monitoring and modelling analyses and as such, land use change calculations, global climate change monitoring and food security analyses suffer. Low resolution, incomplete and often inconsistent land cover data sets signify that the digital representation of the Earth’s biophysical surface is very poor. User generated content is gaining increasing traction within the scientific community; researchers are increasingly looking to Volunteered Geographic Information as a solution to fulfil the inadequacies of authoritative information as it can often be obtained more frequently and with less expense.